Pengaruh Job Burnout terhadap Turnover Intention pada Generasi Milenial Indonesia - Alifah, Qattrunnada; Indiyati, Dian (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Employee intention to leave is an individual's attitude to leave the organization because of fatigue at work, so it makes the intention to leave the company. This study has the goal of knowing the conditions and effects of work fatigue on employee intention to leave in the millennial generation in Indonesia so that it can enrich understanding and thinking about the effect of work fatigue on employee intention to leave, as well as being a company reference in determining strategies to minimize the level of employee intention to leave. The method used is a causal descriptive technique with a quantitative approach. The population of this study is the Indonesian millennial generation. The research sample is three hundred and sixty respondents—data collection using online questionnaires and Structural Equation Model data analysis tools. This study concludes that work fatigue positively and significantly affects employee intention to leave. Thus, it is suggested that the company can seriously handle work fatigue so that there is no intention to leave the company.